The impact of marine heatwaves on rocky intertidal communities: evidence of accumulative carryover effects of marine heatwaves - Ishida, Ken; Tachibana, Michikusa; Yao, Yuan; Wada, Yoko; Noda, Takashi (Frontiers in Marine Science, 2023)
The frequency and duration of marine heat waves (MHWs) have recently increased. There is therefore an urgent need to understand the response of marine organisms to MHWs. However, most estimates of MHW impacts on abundances include the effects of environmental stochasticity other than the MHWs. In addition, although MHWs sometimes persist for year-round or occur repeatedly for shorter periods, the accumulative carryover effects (ACEs)— the effects of sequential events accumulating additively over time— of MHWs on organisms have never been evaluated. Furthermore, the relationship between species niche traits other than thermal niches and susceptibility to MHWs is unknown. We examined the impacts of MHWs in southeastern Hokkaido, northern Japan, in summer from 2010 to 2016 on rocky intertidal communities by distinguishing MHW effects from environmental stochasticity. We asked (1) Did MHWs have ACEs on four major functional groups: macroalgae, sessile invertebrates, herbivorous invertebrates, and carnivorous invertebrates? (2) Does ignoring ACEs lead to biased assessments? (3) How did the effects of the MHWs on functional groups and their subsequent recovery differ? And (4) How does the susceptibility to MHWs differ with species niche (thermal and vertical) traits? We detected ACEs of MHWs and found that if they are ignored, the effects of MHWs can be underestimated. Although MHWs are known to reduce the abundance of macroalgae and increase that of sessile invertebrates in rocky intertidal habitats, our results show that macroalgal abundance increased during and after MHWs, whereas sessile invertebrates showed no change during or after MHWs. The abundance of herbivorous mollusks decreased during and after MHWs. Carnivorous invertebrates declined during MHWs and in the first year after MHWs. During and after MHWs, abundances of species with low thermal niches decreased and those with high thermal niches increased. There were no differences in response to MHWs between vertical niches when accumulative carryover effects were ignored. These results emphasize the importance of considering ACEs when assessing the response of marine organisms to MHWs, and that more studies of these responses are needed for a variety of ecosystems, regions and organisms to predict the responses of marine organisms.